1978
DOI: 10.1128/iai.19.3.792-798.1978
|View full text |Cite
|
Sign up to set email alerts
|

Role of activated macrophages in resistance of congenitally athymic nude mice to hepatitis induced by herpes simplex virus type 2

Abstract: Congenitally athymic nude (nu/nu) mice of a BALB/c genetic background were found considerably more resistant to the induction of focal necrotic hepatitis by herpes simplex virus type 2 (HSV-2) than were phenotypically normal littermates (nu/+) or BALB/c mice. The augmented resistance was age dependent, as it was only manifested in mice from 4 to 5 weeks of age. Studies of the course of infection showed that nude mice were able to restrain virus multiplication in the liver far better than normal mice in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 20 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…The normal response of macrophages from nude mice to priming by LPS and MDP may be a phenomenon which contributes to the surprising ability of nude (nu/nu) mice to survive a challenge infection that is lethal to normal (nu/+) littermates (38)(39)(40). Although the reason for the enhanced survival of nude mice remains unclear (40), one hypothesis is that, in the absence of T-cell-mediated immunity, nude mouse macrophages are exposed to increased amounts of bacterial products, and are thereby chronically activated.…”
Section: Discussionmentioning
confidence: 99%
“…The normal response of macrophages from nude mice to priming by LPS and MDP may be a phenomenon which contributes to the surprising ability of nude (nu/nu) mice to survive a challenge infection that is lethal to normal (nu/+) littermates (38)(39)(40). Although the reason for the enhanced survival of nude mice remains unclear (40), one hypothesis is that, in the absence of T-cell-mediated immunity, nude mouse macrophages are exposed to increased amounts of bacterial products, and are thereby chronically activated.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary characterization using the macrophage inhibitor latex suggests that, as in C57BL/6mice (10), the macrophage is the major peritoneal ADCC effector cell against HSV-infected targets in nude mice ( Table 2). Other studies have similarly revealed enhanced macrophage function of nude mice regard ingviral restriction (17) and tumoricidal activity (15).…”
Section: Discussionmentioning
confidence: 80%
“…route in limited situations (17,26). These authors have attributed this to high levels of interferon production (26) or increased activity of macrophage-viral restriction (17). Added to this list of enhanced early defense mechanisms against HSV is our finding of increased NKC of cells from nude mice to HSV-infected cells ( Table 1, Figs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…an enhanced potential for endocytosis and intracellular killing of some bacteria [3] and for suppression of replication of some viruses [21,27]. An analogous activation was found also in spleen and liver macrophages [14,22].…”
mentioning
confidence: 93%